2021
DOI: 10.3389/fphys.2021.654565
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Dietary Cholesterol in the Kissing Bug Rhodnius prolixus

Abstract: Insects are unable to synthesize cholesterol and depend on the presence of sterols in the diet for cell membrane composition and hormone production. Thus, cholesterol absorption, transport, and metabolism are potential targets for vector and pest control strategies. Here, we investigate the dietary cholesterol absorption and tissue distribution in the kissing bug Rhodnius prolixus using radiolabeled cholesterol. Both the anterior and posterior midguts absorbed cholesterol from the ingested blood, although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Compounds such as azasteroids are known to inhibit the metabolism of sterols in plants (Darnet et al, 2020), nematodes (Choi et al, 2003) and insects either by acting directly on the enzyme Δ 24 -sterol reductase or at some other step in sterol metabolism, transport or utilization (Svoboda and Weirich, 1995). In insects, they block the formation of the moulting hormone or inhibit sterol transport and utilization which is essential for insect growth and development (Entringer et al, 2021;Toprak and Musselman, 2021). A retardation in growth and development due to azasteroids similar to that seen in our study on H. armigera has been reported in many insects (Al-Izzi and Hopkins, 1982;Kuthiala et al, 1987;Goel and Agarwal, 1987;Agarwal et al,1990) and nematode, Caenorhabditis elegans (Choi et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds such as azasteroids are known to inhibit the metabolism of sterols in plants (Darnet et al, 2020), nematodes (Choi et al, 2003) and insects either by acting directly on the enzyme Δ 24 -sterol reductase or at some other step in sterol metabolism, transport or utilization (Svoboda and Weirich, 1995). In insects, they block the formation of the moulting hormone or inhibit sterol transport and utilization which is essential for insect growth and development (Entringer et al, 2021;Toprak and Musselman, 2021). A retardation in growth and development due to azasteroids similar to that seen in our study on H. armigera has been reported in many insects (Al-Izzi and Hopkins, 1982;Kuthiala et al, 1987;Goel and Agarwal, 1987;Agarwal et al,1990) and nematode, Caenorhabditis elegans (Choi et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In some insects growth and development of the larvae was not inhibited even though the analyses of the sterols revealed that the Δ 24 -sterol reductase enzyme was inhibited considerably. It appears then that a significant limitation in availability of cholesterol was not sufficient in itself to disrupt normal development but in addition ecdysteroid biosynthesis or metabolism might also be affected (Svoboda et al, 1972;Tarlochan et al, 1998;Gilbert et al, 2002;Entringer et al, 2021). Larval-pupal intermediates and abnormal wing formation in adults due to azasteroid treatment also indicate that the growth, Figures 3 and 4 show the effect of the second azasteroid, 25-azacoprostane on growth in H. armigera.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In R. prolixus, after feeding, Lp transports diacylglycerol, fatty acids, phospholipids, and cholesterol to the vitellogenic ovaries (Gondim et al, 1989;Santos et al, 2011;Entringer et al, 2021). These lipids are loaded onto circulating Lp at the midgut during blood digestion, but they may also be acquired from the fat body, where-except cholesterol-they may result from de novo lipogenesis (Saraiva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Glycerolipids are carbohydrate-attached lipids that provide energy to all living things [19]. Moreover, cholesterol, although not present in insects, resides in the brain of mammals in the form of myelin [20].…”
Section: Introductionmentioning
confidence: 99%